(3CSS heYGjjQ JUeje GdHQeLjGJ HESJNOGe GdhSGFW GdeJYOOI (B/s - (3MLGRj, aGOjIs ((3HjQhJ(B: s (3OGQ GdfgVI GdYQHjI(B, s, 2006)
(3GdJMhd Yf GdEfJGL GdJbdjOj Edi GdEfJGL GdJaGYdj,GdNWhGJ GdeJHYI aj GdcJGHI dhSGFW YOjOI,JfhY gjGcd HfGI GdeTGQjY,COhGJ GdJCdja hdZGJ GdHQeLI GdNGUI HOeL GdhSGFW,JUeje hGLgI GdeSJNOe,JUeje hEfJGL GdLQGajcS,bhGYO GdedJjejOjG hehGbY GdTHcI GdeYdheGJjI,GdJbjje GdJchjfj aj JUeje HQeLI JYdjejIs
(3HHdjhZQGajG(B:(3U U(B.297-299s
Keywords: (3GdHQeLIs